Association between use of macrolides in pregnancy and risk of major birth defects: nationwide, register based cohort study. (10th February 2021) - Andersson, Niklas Worm; Olsen, Rasmus Huan; Andersen, Jon Trærup
Abstract: Objective: To examine the association between the use of macrolide antibiotics in pregnancy and the risk of major birth defects. Design: Nationwide, register based cohort study. Setting: Denmark, 1997-2016. Participants: Of 1 192 539 live birth pregnancies, pregnancies during which macrolides had been used (13 019) were compared with those during which penicillin (that is, phenoxymethylpenicillin) had been used (matched in a 1:1 ratio on propensity scores). Other comparative groups were pregnancies when macrolides had been used recently but before pregnancy (matched 1:1) and pregnancies where no antibiotics had been used (matched 1:4). Main outcome measures: Association with an outcome of any major birth defect and specific subgroups of birth defects were assessed by relative risk ratios and absolute risk differences. Results: In matched comparisons, 457 infants were born with major birth defects to women who had used macrolides during pregnancy (35.1 per 1000 pregnancies) compared with 481 infants (37.0 per 1000 pregnancies) to women who had used penicillin (relative risk ratio 0.95; 95% confidence interval 0.84 to 1.08), corresponding to an absolute risk difference of −1.8 (95% confidence interval −6.4 to 2.7) per 1000 pregnancies. The risk of major birth defects was not significantly increased for women who had used macrolides during pregnancy compared with those who had used macrolides recently but before becoming pregnant (relative risk ratio 1.00 (95% confidence interval 0.88 to 1.14); absolute risk difference −0.1 (95% confidence interval −4.8 to 4.7) per 1000 pregnancies) or compared with women who did not use any antibiotics (1.05 (0.95 to 1.17); 1.8 (−1.7 to 5.3) per 1000 pregnancies). For all three comparative group analyses and in the analyses of use of individual macrolides, no significant increased risk of specific subgroups of birth defects associated with the use of macrolides was found. Conclusions: In this nationwide cohort study, the use of macrolide antibiotics in pregnancy was not associated with an increased risk of major birth defects. Analyses of the associated risk of 12 specific subgroups of birth defects with the use of macrolides in pregnancy were not significant.